Generation of simulated corium using thermite process. (1st December 2021) - Hemanth Rao, E.; Shukla, Prabhat Kumar; Venkat Reddy, G.; Murthy, S.S.; Kumaresan, M.; Das, Sanjay Kumar; Lydia, G.; Ponraju, D.; Athmalingam, S.; Venkatraman, B.
Highlights: An experimental program is taken up to investigate severe accident phenomena in SFRs THEME test facility is setup to generate simulated corium to study severe accidents. Experiments are conducted on progression of melt in a simulated fuel subassembly. Experiments are performed on fragmentation of simulated corium in water. Alumina/ YSZ coatings can protect core catcher substrate from high temp melt attack. Abstract: Nuclear reactors are built with many inherent and engineered safety features with defence in depth philosophy, to maintain integrity of core during normal as well as accidental conditions. However, a severe accident scenario such as hypothetical core meltdown has to be considered in safety analysis of the plant, towards demonstrating a safe and coolable geometry of degraded core. Progression of corium, its subsequent interaction with coolant and settlement in the reactor vessel determines the extent of core damage and needs thorough investigation for ensuring safe mitigation of the accident. A comprehensive experimental program has been taken up at IGCAR to investigate severe accident phenomena in Sodium cooled Fast Reactors (SFR). Highly exothermic thermite reaction is used to generate a high temperature melt consisting of ceramic and iron simulating the corium. A dedicated test facility 'THEME' has been setup and few small scale simulation experiments were conducted to study various phenomena like subassembly melting, corium interaction with coolant and settlement of debris on corecatcher.